In-Class Formative Assessment in an Introductory Calculus Class - Menny Aka; Meike Akveld; Alexander Caspar; Gerd Kortemeyer; Marinka Valkering-Sijsling (FernUniversität Hagen, 2020)
We report on the usage of an audience response system ("clickers") in an introductory math course, both in terms of practical usage and in terms of answer distributions, test-theoretical properties and clustering of questions. We give examples of the questions ("items") that we used and their associated properties. We found the system to deliver meaningful and reliable results regarding the conceptual learning of the students, and we found these benefits to be robust independent of the particulars of the instructional setting. Finally we found that peer instruction can make clicker usage even more meaningful, as the discrimination of questions increases after discussions between learners.